Correlation Between Implementation Intensity of Internal Quality Control and the Outcome of External Quality Control at Public Health Center Laboratories - Anik Handayati; Ni Wayan Lisna Marheni (Humanistic Network for Science and Technology (HNST), 2021)
Quality control is a process in a procedure conducted to evaluate testing process, with the purpose of ensuring the outcome of laboratory examinations, minimizing, as well as identifying the source of deviations. It consists of two, the internal and external quality control. This study aims to determine correlation between implementation intensity of internal quality control and the outcome of external quality control in the parameter of complete blood count in Public Health Centers Laboratories in Gianyar Bali. This study was a correlational observational study with cross-sectional approach. Total samples of 13 laboratories were taken from total population. As many as 15.38% of Public Health Center carried out internal quality control every day, 53.85% once a week, 7.7% biweekly, and 23.07% carried it out once a month. As for external quality control with parameter of complete blood count, 61.54% of the centers were good, 23.07% were average, and 15.38% were poor in handling abnormally low level of complete blood count. At normal level, 76.92% were good, 15.38% in average, and 7.7% were below average. At abnormally high level, 53.85% were good and 46.15% were in average. Statistical test results showed p-value >0.05. It can be concluded that there is no correlation between implementation intensity of internal quality control and the outcome of external quality control with parameter of complete blood count in Public Health Center laboratories in Gianyar Bali. Keywords: internal quality control; external quality control; complete blood count